Crystal Growth and Characterization of the Non-Centrosymmetric Hydrated Co-hexaborate templated by racemic 2-methylpiperazinium (C5H14N2){Co[B6O7(OH)6]2}.2H2O - Akriche, Samah; Tliba, Aymen; Rzaigui, Mohamed (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Large single crystals of the non-centrosymmetric hydrated Co-hexaborate (C5H14N2){Co[B6O7(OH)6]2}.2H2O were grown from aqueous solution and characterized by powder and single-crystal XRD methods, IR, UV-Vis and photoluminescence spectroscopy measurements. Single-crystal XRD analyses show that the reported compound crystallizes in the orthorhombic non-centrosymmetric space group Fdd2 and its crystal structure consists of anionic molecular Co-hexaborate units arranged into 3D-supramolecular honey-comb like structure network with the organic cation and water of crystallization occupying large tunnels voids along [110] through strong hydrogen bond interactions. In addition, Its electronic properties have also been investigated showing a considerable important gap energy well proving the semiconductor behavior and the photoluminescent property of reported material.